Personalized Environmental Control Systems (PECS): Systematic review of benefits for thermal comfort, air quality, health, and human performance - Dolaana Khovalyg; Mariya P. Bivolarova; Jun Shinoda; Douaa Al-Assaad; Marika Vellei; Karol Bandurski; Giorgia Chinazzo; Ongun B. Kazanci; Joyce Kim; Tobias Kramer; Aleksandra Lipczynska; Shichao Liu; et al. (Building and Environment, 2025)

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Seasonal dynamics of the wild rodent faecal virome - Jayna Raghwani; Christina L. Faust; Sarah François; Dung Nguyen; Kirsty Marsh; Aura Raulo; Sarah C. Hill; Kris V. Parag; Peter Simmonds; Sarah C. L. Knowles; Oliver G. Pybus (Molecular Ecology, 2023)
Viral discovery studies in wild animals often rely on cross‐sectional surveys at a single time point. As a result, our understanding of the temporal stability of wild animal viromes remains poorly resolved. While studies of single host–virus systems indicate that host and environmental factors influence seasonal virus transmission dynamics, comparable insights for whole viral communities in multiple hosts are lacking. Utilizing noninvasive faecal samples from a long‐term wild rodent study, we characterized viral communities of three common European rodent species ( Apodemus sylvaticus , A. flavicollis and Myodes glareolus ) living in temperate woodland over a single year. Our findings indicate that a substantial fraction of the rodent virome is seasonally transient and associated with vertebrate or bacteria hosts. Further analyses of one of the most common virus families, Picornaviridae, show pronounced temporal changes in viral richness and evenness, which were associated with concurrent and up to ~3‐month lags in host density, ambient temperature, rainfall and humidity, suggesting complex feedbacks from the host and environmental factors on virus transmission and shedding in seasonal habitats. Overall, this study emphasizes the importance of understanding the seasonal dynamics of wild animal viromes in order to better predict and mitigate zoonotic risks.

Large scale and sub-regional connections in the lead up to summer heat wave and extreme rainfall events in eastern Australia - Ghyslaine Boschat; Alexandre Pezza; Ian Simmonds; Sarah Perkins; Tim Cowan; Ariaan Purich (Climate Dynamics, 2015)

Constraints on temperature-dependent sex determination in the leopard gecko (Eublepharis macularius): response to Kratochvil et al. - Victoria Huang; Jon T. Sakata; Turk Rhen; Patricia Coomber; Sarah Simmonds; David Crews (The Science of Nature, 2008)